TEACHING LITERATURE TO ADOLESCENTS: FROM TEXT TO MULTILITERACIES AND DIGITAL MEDIA - Dila Charisma; Rahayu Puji Haryanti; Azran Azmee Kafia (University of Kuningan, 2025)
In an era when adolescents are immersed in digital spaces, traditional practices of teaching literature in class fail to address their multimodal beings. Multiliteracies pedagogy is growing to be known, yet it has not been extensively developed in tertiary EFL settings, especially in Southeast Asia. There has been little investigation into how undergraduate students make sense of traditional texts in digital spaces. This study investigates the integration of online poster creation and character monologue video production in the teaching of traditional short stories to adolescent EFL students for enhanced literary comprehension and personal identification. With a classroom qualitative design, 24 Indonesian fourth-semester English Education students from Muhammadiyah University in West Java reviewed two stories, Araby and Mademoiselle Fifi, through Canva-based posters and performative video monologues. Student work and interview data were examined thematically to look for engagement and interpretation trends. The results indicate that the students not only accessed deeper symbolic meaning and empathic understanding but also enacted and represented personal and cultural identities through the visual and performative modes. The multimodal tasks enabled critical reading of themes such as disillusionment, gender, and nationalism, and transformed the students into active readers of literature. This research establishes the pedagogic worth of digital technology in teaching literature. By leveraging the digital literacy of adolescent students, instructors can facilitate more sophisticated literary consciousness and construct critical, creative readers in EFL environments.